2015
DOI: 10.1063/1.4917567
|View full text |Cite
|
Sign up to set email alerts
|

Current transport mechanisms in plasma-enhanced atomic layer deposited AlN thin films

Abstract: Here, we report on the current transport mechanisms in AlN thin films deposited at a low temperature (i.e., 200°C) on p-type Si substrates by plasma-enhanced atomic layer deposition. Structural characterization of the deposited AlN was carried out using grazing-incidence X-ray diffraction, revealing polycrystalline films with a wurtzite (hexagonal) structure. Al/AlN/ p-Si metal-insulator-semiconductor (MIS) capacitor structures were fabricated and investigated under negative bias by performing current-voltage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 26 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…[201][202][203][204] Interestingly, recent investigations of the electrical properties of sputter deposited and PEALD AlN have also reported electrical leakage to occur predominantly by the PF mechanism. [205][206][207] More recent electrically detected magnetic resonance (EDMR) measurements by Mutch et al have conclusively shown that electron transport in PECVD SiN:H specifically occurs through silicon dangling bond defect states located in the mid-upper portion of the SiN bandgap. 208,209 Owing to the similar IV characteristics, deduced leakage mechanism, and band structure, 210 it seems plausible that electron transport in amorphous AlN (independent of deposition method) may also occur through Al dangling bond defect states.…”
mentioning
confidence: 99%
“…[201][202][203][204] Interestingly, recent investigations of the electrical properties of sputter deposited and PEALD AlN have also reported electrical leakage to occur predominantly by the PF mechanism. [205][206][207] More recent electrically detected magnetic resonance (EDMR) measurements by Mutch et al have conclusively shown that electron transport in PECVD SiN:H specifically occurs through silicon dangling bond defect states located in the mid-upper portion of the SiN bandgap. 208,209 Owing to the similar IV characteristics, deduced leakage mechanism, and band structure, 210 it seems plausible that electron transport in amorphous AlN (independent of deposition method) may also occur through Al dangling bond defect states.…”
mentioning
confidence: 99%
“…This indicates that metal–nitrogen and metal–hydride bonds designed into the precursor successfully respectively reduced carbon and oxygen contamination in AlN films. This is especially noteworthy when other processes using TMA and NH 3 plasma have employed plasma pulse lengths of 40 s to reduce impurities in AlN films.…”
Section: Results and Discussionmentioning
confidence: 54%
“…This indicates that metal-nitrogen and metal-hydride bonds designed into the precursor successfully respectively reduced carbon and oxygen contamination in AlN films. This is especially noteworthy when other processes using TMA and NH3 plasma have employed plasma pulse lengths of 40 seconds [15][16][17][18] in order to reduce impurities in AlN films.…”
Section: Resultsmentioning
confidence: 99%